SUSTAINABILITY OF LOCAL CORN FROM THE PERSPECTIVE OF FARMERS IN DUKO TAMBIN VILLAGE, BANGKALAN REGENCY - Lutfiyah; Mubarokah; Dona Wahyuning Laily (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research analyzes the sustainability of local corn farming from the farmers' perspective in Duko Tambin Village, Bangkalan Regency, Madura. The approach used is qualitative descriptive-analytical with data triangulation. Data were collected through in-depth interviews and analyzed using NVivo software. The results show that farmers' perceptions regarding the sustainability of local corn are divided into four main dimensions: economic, ecological, social and cultural, and technological. Economically, farmers continue to cultivate local corn despite low income because of cheap production costs, land ownership, and easy marketing. From an ecological perspective, local corn is considered drought-resistant and more environmentally friendly, although it still faces challenges from pest attacks and the use of chemical pesticides. Socially, family values and farmer solidarity persist, although mutual assistance practices are beginning to fade. From a cultural aspect, local corn has symbolic value and is cultivated through generations, but it is threatened by shifting preferences of the younger generation and modernization. In terms of technology, limited access to information, training, and costs make it difficult for farmers to adopt new innovations. This research concludes that the sustainability of local corn is more supported by cost efficiency, local wisdom, and ecological adaptation, compared to systemic support or modern technology.